Reconstructing the Enforcement Power of Civil Judgments through a National Enforcement Officer to Achieve Effective Judicial Enforcement - A. Wafi; Ellydar Chaidir; Efendi Ibnususilo; Suparto Suparto; Surizki Febrianto (Jurnal El-Thawalib, 2026)
This study examines the crisis of enforcement efficacy in the Indonesian civil justice system—a structural irony in which the coercive power of state bailiffs has proven ineffective. Even when a judicial decision has attained the status of inkracht van gewijsde (final and binding), empirical evidence reveals a stagnation in the realization of rights, thereby fundamentally undermining the essence of legal protection for litigants. Employing a normative legal research methodology grounded in conceptual, statutory, and cross-jurisdictional comparative approaches, the study utilizes primary legal sources (legislation and relevant legal instruments), secondary sources (scholarly journals from the last decade, legal doctrine or communis opinio doctorum, and official reports), and tertiary sources; data were collected via documentation techniques and analyzed using a deductive-qualitative method. The findings indicate that reconstructing enforcement power through a "National Enforcement Officer" model is essential to bridge the gap between court judgments and the actual realization of the prevailing party's rights. This model enhances the professionalism of enforcement officials, inter-agency coordination, and the oversight of enforcement proceedings, ensuring they operate effectively and proportionately. Consequently, enforcement ceases to be merely an administrative stage and becomes an integral component of effective judicial enforcement, guaranteeing the actual implementation of court rulings